HUBUNGAN FAMILY SUPPORT DENGAN WORK LIFE BALANCE PADA IBU PEKERJA DI PERUSAHAAN SWASTA - Fajrah Fadhilla; Ayu Lodiana (Counseling Milenial (CM), 2024)
Work-life balance is a challenge for working mothers, especially in private companies with high job demands. Family support is believed to play a crucial role in helping working mothers achieve a balance between their work and personal lives. This study aims to examine the relationship between family support and work-life balance among working mothers in private companies in Medan, Indonesia. This research employs a quantitative correlational approach. The sample consists of 200 working mothers employed in private companies in Medan, selected using purposive sampling. Data collection was conducted using the Family Support Scale (FSS) and the Work-Life Balance Scale (WLBS). Pearson correlation analysis was used to determine the relationship between these two variables. The results show a significant positive correlation between family support and work-life balance (r = 0.68, p < 0.01). This indicates that the higher the family support, the better the work-life balance experienced by working mothers. These findings highlight the crucial role of family in assisting working mothers in managing their dual roles more effectively.